2014
DOI: 10.1148/rg.343135059
|View full text |Cite
|
Sign up to set email alerts
|

Update on Imaging of the Postsurgical Breast

Abstract: Oncologic, reconstructive, and cosmetic breast surgery has evolved in the last 20 years. Familiarity with cutting-edge surgical techniques and their imaging characteristics is essential for radiologic interpretation and may help avert false-positive imaging findings. Novel surgical techniques include skin- and nipple-sparing mastectomies, autologous free flaps, autologous fat grafting, and nipple-areola-complex breast reconstruction. These techniques are illustrated and compared with conventional surgical tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(28 citation statements)
references
References 64 publications
0
25
0
1
Order By: Relevance
“…Since mammograms are not adversely affected after aesthetic breast reduction, surveillance mammograms after OBCS may also not be impeded [15]. Losken et al [4] demonstrated that ‘mammographic stabilisation' is delayed after OBCS compared to WLE, but that overall mammographic findings, including architectural distortion, cysts, and calcification, are similar.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since mammograms are not adversely affected after aesthetic breast reduction, surveillance mammograms after OBCS may also not be impeded [15]. Losken et al [4] demonstrated that ‘mammographic stabilisation' is delayed after OBCS compared to WLE, but that overall mammographic findings, including architectural distortion, cysts, and calcification, are similar.…”
Section: Discussionmentioning
confidence: 99%
“…Monticciolo et al [10] showed that mammographic findings are predictive even after volume replacement with a mini-latissimus dorsi flap. Common mammographic changes visible after OBCS include parenchymal redistribution, dermal calcification along the skin incisions and repositioned nipples, and fibrous bands extending to the nipple-areola complex [15]. Mammographic microcalcification is rarely a confounding factor after OBCS, unless it is followed or accompanied by autologous fat grafting.…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary data suggest that newer generations of silicone implants may have a lower incidence of rupture, although data from longer follow-up periods are needed (8). Silicone implants are now commonly used in implant reconstruction because the increased density facilitates shape maintenance (4).…”
Section: Patientsmentioning
confidence: 99%
“…In the case of the abdominal excess transferred in the DIEP flap, a pedicle is dissected in the muscle, and there is absolutely no muscle within the flap (hence the name perforator flap). The harvested tissue is then connected to the recipient site by an anastomosis, with microsurgical sutures performed under the microscope: the deep inferior vessels are ligated to the internal mammary vessels lying under the cartilage of the third or fourth rib [15]. The techniques required for perforator flaps are more complex, with a significantly longer operating time, than those involved in the placement of a conventional pedicled flap [16,17].…”
Section: Autologous Flaps General Considerationsmentioning
confidence: 99%
“…The classic MRI findings of a fat-injection site include hyperintensity on non-fat-saturated T1-weighted images, hypointensity on fat-saturated images, and hypointensity on T2-weighted images [15]. Three types of abnormalities as seen on MRI have been described: 1.…”
Section: Imaging Featuresmentioning
confidence: 99%